The secret she keeps - Diaz, Lena (Diaz, Lena. Tennessee cold case story., 2023)
"Raine Quintero is so desperate she's willing to kidnap PI Callum Wright, the one person who can help stay her brother's execution. Raine raises the stakes by offering a lead on a killer Callum's pursuing--without revealing the secret she's actually keeping. Racing against time, they must find the answers before one man dies--and another kills again."--